2007
DOI: 10.1103/physreva.75.032305
|View full text |Cite
|
Sign up to set email alerts
|

Simulating a single-qubit channel using a mixed-state environment

Abstract: We analyze the class of single qubit channels with the environment modeled by a one-qubit mixed state. The set of affine transformations for this class of channels is computed analytically, employing the canonical form for the two-qubit unitary operator. We demonstrate that, 3 8 of the generalized depolarizing channels can be simulated by the one-qubit mixed state environment by explicitly obtaining the shape of the volume occupied by this class of channels within the tetrahedron representing the generalized d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 21 publications
0
32
1
Order By: Relevance
“…A number of explicit counterexamples have subsequently disproved the validity of this conjecture [23,24,25]. Interestingly, we find that a version of the above conjecture does hold true, provided that additional classical randomization resources, as well as non-deterministic channel constructions, are allowed (Section 3.3).…”
Section: Arxiv:170401486v1 [Quant-ph] 5 Apr 2017mentioning
confidence: 79%
See 1 more Smart Citation
“…A number of explicit counterexamples have subsequently disproved the validity of this conjecture [23,24,25]. Interestingly, we find that a version of the above conjecture does hold true, provided that additional classical randomization resources, as well as non-deterministic channel constructions, are allowed (Section 3.3).…”
Section: Arxiv:170401486v1 [Quant-ph] 5 Apr 2017mentioning
confidence: 79%
“…However, this conjecture has been proven wrong in Refs. [23,24,25]: one may explicitly identify CPTP maps that need a larger (at least d S + 1 dimensional) ancilla in order to be implemented via unitary design as in Eq. (3).…”
Section: Probabilistic Unitary Designmentioning
confidence: 99%
“…The set of unistochastic maps, denoted by U Q N , forms a proper subset of the set B Q N of bistochastic maps. In the one-qubit case, the set of bistochastic maps forms the tetrahedron of Pauli channels Φ ⃗ p , while U Q 2 , forms its non-convex subset, bounded by ruled surfaces [19,42] and called Steinhaus tetrahedron [43] -see Fig. 1 and ref.…”
Section: Bistochastic Quantum Maps and Classical Bistochastic Matricesmentioning
confidence: 99%
“…Furthermore, recently, Ref. [16] has shown that only 3/8 of the generalized depolarizing channels can be simulated by the one-qubit mixedstate environment.…”
Section: Introductionmentioning
confidence: 99%